2004
DOI: 10.1007/s00167-004-0522-8
|View full text |Cite
|
Sign up to set email alerts
|

The Oxford unicompartmental knee prosthesis: a 2?14�year follow-up

Abstract: Our medium- and long-term results obtained with the Oxford unicompartmental knee prosthesis for unicompartmental knee osteoarthrosis are presented. Ninety-seven prostheses were evaluated (87 medial, 10 lateral) in 86 patients, with the Hospital for Special Surgery knee score after 2-14 years (mean follow-up: 6 years 9 months). Five prostheses were lost to follow-up. Eight patients died, not related to surgery; none had undergone a revision. Fourteen revisions (of which one bilateral UKP), 11 medial and three l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
0
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 19 publications
(39 reference statements)
2
29
0
2
Order By: Relevance
“…Our revision rate of 4.3% at a mean 42.6 months (range, 12-102 months) is comparable to rates in previous studies [3,5,9,10,12] and is consistent with the documented revision rates for UKA in Australia [1]. Some studies report higher rates of revision ranging between 12% and 15% [2][3][4]12]. An aspect of this study rarely reported in the literature is the revision of a UKA to a second UKA [5,7].…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Our revision rate of 4.3% at a mean 42.6 months (range, 12-102 months) is comparable to rates in previous studies [3,5,9,10,12] and is consistent with the documented revision rates for UKA in Australia [1]. Some studies report higher rates of revision ranging between 12% and 15% [2][3][4]12]. An aspect of this study rarely reported in the literature is the revision of a UKA to a second UKA [5,7].…”
Section: Discussionsupporting
confidence: 90%
“…However, given that the median time from the index surgery to reintervention was 13 months, it is likely this underestimation of the reintervention rate is low. The revision rate for UKA is greater than for TKA [2,3,5,6,12], and recent Australian data show primary UKAs have a 5-year cumulative revision rate of 8.9%, whereas the 5-year cumulative revision rate for TKA is 3.6% [1]. Patients undergoing UKA generally have less marked disease than patients undergoing primary TKA, and as such, probably are less tolerant of imperfection, leading to complaints and intervention at an earlier stage.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been suggested that UKA should result in a more normal restoration of knee function compared with TKA because the procedure requires less soft tissue dissection and both cruciate ligaments are preserved [7,14]. However, studies on survival rates and clinical measures (eg, Knee Society scores) of UKA demonstrate mixed results [3,12,15,28,30], and some evidence of early failure rates has been reported [21]. Therefore, some surgeons are reluctant to use this procedure as a result of conflicting evidence of effectiveness [3,12,15,28,30].…”
Section: Introductionmentioning
confidence: 99%